LINGUOCULTUROLOGICAL PECULIARITIES OF THE HISTORICAL MONUMENTS OF SHAHRISABZ (International journal of artificial intelligence, 2025)
The article examines the linguoculturological features of historical monuments in Shakhrisabz, focusing on epigraphic inscriptions, architectural symbolism, and cultural concepts. The research reveals the role of language in shaping historical memory and cultural identity.